Innovations in IBS Treatment: From Gut-Brain Therapies to Microbiome Modulation - Nitschke, Nicole; Mocarska, Martyna; Orłowska , Anna; Strakowska, Katarzyna; Opalska, Laura; Maryńczak , Anna; Muciek, Adrianna; Mencel, Jan (Quality in Sport, 2025)
Irritable Bowel Syndrome (IBS) is a chronic gastrointestinal disorder characterized by abdominal pain, bloating, and altered bowel habits. It affects a significant portion of the global population and often leads to a diminished quality of life. Despite its relatively high prevalence, the exact cause of IBS remains unclear, making effective treatment challenging. Traditional approaches, including dietary modifications, fiber supplements, and antispasmodic medications, have offered relief for some but not all patients. In recent years, new treatment strategies have emerged, targeting the underlying mechanisms believed to contribute to IBS. These include gut-brain axis therapies such as cognitive behavioural therapy (CBT) and hypnotherapy, microbiome-based treatments like faecal microbiota transplantation (FMT) and targeted probiotics, and novel pharmacological agents aimed at modulating serotonin signalling and intestinal motility. Advances in personalized medicine are also playing a growing role, enabling clinicians to tailor treatments based on individual symptom profiles and microbiome composition. These developments represent a promising shift toward more effective and patient-centred management of IBS.